Ultrafast high-harmonic nanoscopy of magnetization dynamics - Sergey Zayko (Nature Portfolio, 2021)
Light induced magnetization dynamics can be as fast as few tens of femtoseconds. Here, Zayko et al show ultrafast microscopy based on high-harmonic radiation for direct imaging of ultrafast phenomena and capture femtosecond spin dynamics at the nanoscale.